2017
DOI: 10.1177/0957650917721595
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of in situ combustion and gasification

Abstract: The total worldwide resources of oil sands, heavy oil, oil shale and coal far exceed those of conventional light oil. In situ combustion and gasification are techniques that can potentially recover the energy from these unconventional hydrocarbon resources. In situ combustion can be used to produce oil, especially viscous and immobile crudes, by heating the oil and reducing the viscosity of the hydrocarbon liquids allowing them to flow to production wells. In situ gasification can be used to convert deep carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The shaft-less (drilling-type) UCG mode is to use drilling technology to build injection and production wells in the coal seam, and then establish a gasification channel between the two wells by linking methods including reverse combustion, electric resistive heating, hydraulic fracturing, and directional drilling [9,10]. As shown in Figure 1, the drilling-type UCG mode can be divided into the linked-vertical-wells (LVW) technique and controlled-retractable-injection-point (CRIP) technique according to the layout of gas injection wells.…”
Section: Cavity Growth Mechanismmentioning
confidence: 99%
“…The shaft-less (drilling-type) UCG mode is to use drilling technology to build injection and production wells in the coal seam, and then establish a gasification channel between the two wells by linking methods including reverse combustion, electric resistive heating, hydraulic fracturing, and directional drilling [9,10]. As shown in Figure 1, the drilling-type UCG mode can be divided into the linked-vertical-wells (LVW) technique and controlled-retractable-injection-point (CRIP) technique according to the layout of gas injection wells.…”
Section: Cavity Growth Mechanismmentioning
confidence: 99%
“…The results showed that the relative error between the calculated value and the measured value was below 15 %, except for the measured points near the flameworking face. The combustion mathematical modeling and in situ gasification was described in [12]. Chemical reactions in multiphase porous media were simulated in this work.…”
Section: Introductionmentioning
confidence: 99%